2022
DOI: 10.3390/cells11233758
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 and Gut Microbiota Homeostasis: Progress in Research

Abstract: The inflammasome is a platform for inflammatory signaling, and the NLRP3 inflammasome recognizes stimuli in vitro and in vivo, and releases inflammatory cytokines that trigger inflammation and pyroptosis. In the gut, the NLRP3 inflammasome is a key sensor for protecting the body from damage and exogenous pathogens. It plays a fundamental role in maintaining the stability of the gut’s immune system. We focus on the role of NLRP3 as a key node in maintaining the homeostasis of gut microbiota which has not been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…A strong correlation between intestinal flora and diabetes began to reveal. Recent studies have shown that the intestinal flora plays an important role in maintaining gut homeostasis, especially in the regulation of inflammation (5). Through the interaction with dietary components, it affects intestinal permeability, glucose homeostasis, insulin sensitivity, glucose lipid metabolism and so on (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation between intestinal flora and diabetes began to reveal. Recent studies have shown that the intestinal flora plays an important role in maintaining gut homeostasis, especially in the regulation of inflammation (5). Through the interaction with dietary components, it affects intestinal permeability, glucose homeostasis, insulin sensitivity, glucose lipid metabolism and so on (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…NLRP3 Inflammasome can recognize a wide range of stimuli in vitro and in vivo, and release inflammatory cytokines, which can trigger inflammation. NLRP3 inflammasome plays an important role in maintaining the intestinal health by protecting ( Pan et al, 2022 ). However, chronical or excessive activation of NLRP3 inflammasome can lead to various inflammatory diseases ( Zheng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier PRRs, such as TLRs and nucleotide-binding oligomerization (NOD)-like receptors (NLRs) amongst many others, also sense microorganisms through PAMPs like lipopolysaccharide (LPS), lipoproteins, peptidoglycan, and lipoteichoic acid (LTA) to control homeostatic tolerance to commensal microbes and host responses to potential microbial threats [16]. Recognition of LTA and LPS from various gram-positive and gram-negative microbes activates TLRs and drives GIM-related inflammation after formation and activation of the NLRP3 inflammasome and pyroptotic cell death [20 ▪ ]. Activation of NF-ĸB by TLR signaling through MyD88-dependent and -independent pathways is another important mechanism of inflammation.…”
Section: Gastrointestinal Mucositis As Sign Of Local Inflammationmentioning
confidence: 99%